Problematika, Tantangan dan Solusinya Perekrutan Badan Ad Hoc Pada Penyelenggaran Pemilu 2024 - Dede Nuryayi Taufik (CV Putra Publisher, 2023)
In holding a general election there are organizers who have an important role as election officers at the lower level, namely at the sub-district and village levels, namely PPK, PPS, KPPS, Panwascam, PKD and TPS Panwas. The factor that will determine the fulfillment of the HR (Human Resources) qualifications needed in filling these positions is recruitment. This research intends to discuss the problems, challenges and solutions of election management recruitment at the grassroots level. The method used in this article is a qualitative descriptive method. The primary data source used is research journals on Election Implementation. Data collection techniques using journals and books. Data analysis using content analysis. The results of this study indicate that at the stage of selecting ad hoc election bodies, there are obstacles that are often encountered during the selection process, namely the difficulty of getting qualified selectors, honest and able to provide an objective assessment. Not a few were found in the field, selectors give value on the basis of their role and not on the basis of their thoughts, apart from that the closeness factor is very difficult to ignore. The concept of Training of Trainers is a breakthrough in providing understanding to ad hoc committees at least at the sub-district and sub-district/village levels so that these ad hoc committees are able to solve problems in the field and understand the ethical standards of implementation.